Profesores, científicos e intelectuales : la Universidad de Buenos Aires de 1955 a su Bicentenario - Unzué, Martín (Colección IIGG-CLACSO, 2020)
This book proposes a reflection on the complex role that universities have in our recent histories, based on the question of the ways in which they receive and participate in the political, economic and cultural processes in which they are immersed. Centered on the case of the University of Buenos Aires, at the gates of the bicentennial of its foundation, Professors, Scientists and Intellectuals expresses an analysis of the role that the UBA has assumed in Argentine history since 1955, at times broken down into the ways in which their professors and professors have built public positions that are rarely exempt from contradictions and resistance. The research that is synthesized here partially reconstructs the course of these decades, discusses some of the canonical readings and opens a space for debates about a future that is not only that of that university or the university system.